Hunter-gatherers adjust mobility to maintain contact under climatic variation. (June 2018) - Grove, Matt
Abstract: Population density and mobility are fundamental population parameters for hunter-gatherer groups, and their reconstruction for prehistoric populations has long been an aim of archaeological research. This endeavour has become more important than ever in recent years, with the recognition that these parameters play a key role in determining rates of cultural transmission. Potential archaeological proxies for population density and mobility are often hard to interpret, creating a need for more generic, reliable, and easily calculated indicators. Climatic variables provide considerable promise in this area, and the analyses reported here test the efficacy of six climatic variables as potential predictors. Significant predictors are then incorporated in path analyses that assess the causal relationships between climatic variables, population density, and mobility. Results suggest that the previously established strong reciprocal relationship between population density and mobility is not due purely to common determination by climatic variables. Instead, the best supported model is consistent with the hypothesis that hunter-gatherers adjust levels of mobility so as to maintain contact with neighbouring groups at varying population densities. This ensures that opportunities for cultural transmission are maintained at similar levels regardless of climatic variation. The results lead to a number of archaeologically testable predictions concerning the relationships between climatic variables, population density, mobility, and assemblage complexity. Highlights: Climatic variables directly predict hunter-gatherer population densities. Mobility is adjusted in response to population density. This results in an optimised, consistent level of connectivity. Cultural transmission is therefore robust to climatic variation.